Demonstrasi Kimia Sederhana sebagai Media Edukasi Sains dalam Meningkatkan Minat dan Rasa Ingin Tahu Anak TK dan SD - Akram La Kilo; Wiwin Rewini Kunusa (Universitas Negeri Gorontalo, 2026)
Science education at an early age plays an important role in fostering scientific literacy, curiosity, and interest in learning. However, science learning for kindergarten and elementary school children is often delivered through conventional approaches that provide limited opportunities for direct exploration and experimentation. This community service program aimed to implement simple chemistry demonstrations as an interactive science education medium to enhance children's interest and curiosity toward science. The program was conducted through the Gorontalo Expolaboratorium – Science for Kidz at the Integrated Laboratory of Universitas Negeri Gorontalo, involving 17 kindergarten and elementary school students from six schools in Gorontalo Province. The activities adopted an experiential learning approach combined with inquiry-based learning, featuring five simple chemistry demonstrations: Lava Lamp, Balloon Inflation, Elephant Toothpaste, Invisible Ink, and Dragon's Breath. Program evaluation employed descriptive qualitative analysis supported by quantitative data collected through observations, documentation, participant engagement, and satisfaction surveys. The results showed that all participants completed the entire program with a high level of enthusiasm and active participation. Approximately 80% of participants and their parents expressed satisfaction with the activities. The demonstrations successfully stimulated children's curiosity, encouraged them to ask questions, participate in discussions, and relate scientific phenomena to everyday experiences. Furthermore, the program enhanced the pedagogical competencies of graduate students serving as facilitators in communicating scientific concepts to young learners. These findings indicate that simple chemistry demonstrations provide an effective, enjoyable, and experiential approach to introducing science concepts and promoting scientific literacy among young children